Reviewing Design Process Theories, Discourses in Architecture, Urban Design and Planning Theories. - Rezaei, Mahmud (Springer, 2021)
This interdisciplinary book explores design theories, combining research from a range of fields including architecture, landscape architecture, urban planning, urban design, industrial design, software engineering, environmental psychology, geography, anthropology, and sociology. Following an extensive review of the current literature, the author reveals eight major types of theory in design processes. The theories are classified as follows: Rational vs. Empiricist Theories, Procedural vs. Substantive Theories, Normative vs. Positive Theories, Design Scopes, Designers vs. People, Form and Space Creation Paradigms, Efficient Tools and Sources in the Design Process, and Place vs. Non-Place Theories. The respective design theories are illustrated with diagrams, tables and figures, condensing the content of over 140 essential theoretical texts that address various aspects of design processes. Given its scope, the book will appeal to undergraduate and graduate students, and to researchers and practitioners in design, urban planning, urban design, architecture, art, etc.
Keywords: Stadtplanung; Landschaftsplanung; Architektur; Entwurfslehre; Entwerfen; Entwurfsprozess; Planungstheorie; Gestaltungslehre; Design; Ortsbezogenheit; Interdisziplinarität; Theorieansatz